Differential Impacts of Soybean and Fish Oils on Hepatocyte Lipid Droplet Accumulation and Endoplasmic Reticulum Stress in Primary Rabbit Hepatocytes - Xueping Zhu; Zhihui Xiao; Yumin Xu; Xingli Zhao; Ping Cheng; Ningxun Cui; Mingling Cui; Jie Li; Xiaoli Zhu (Gastroenterology Research and Practice)
Parenteral nutrition-associated liver disease (PNALD) is a severe ailment associated with long-term parenteral nutrition. Soybean oil-based lipid emulsions (SOLE) are thought to promote PNALD development, whereas fish oil-based lipid emulsions (FOLE) are thought to protect against PNALD. This study aimed to investigate the effects of SOLE and FOLE on primary rabbit hepatocytes. The results reveal that SOLE caused significant endoplasmic reticulum (ER) and mitochondrial damage, ultimately resulting in lipid droplets accumulation and ER stress. While these deleterious events induce hepatocyte injury, FOLE at high doses cause only minor ER and mitochondrial damage, which has no effect on hepatic function. SOLE also significantly upregulated glucose-regulated protein 94 mRNA and protein expression. These data indicate that SOLE, but not FOLE, damage the ER and mitochondria, resulting in lipid droplets accumulation and ER stress and, finally, hepatocyte injury. This likely contributes to the differential impacts of SOLE and FOLE on PNALD development and progression.